TEACHING ARABIC BY USING ELECTIVE METHOD TO IMPROVE STUDENTS READING SKILL AT THE NATIONAL HIGH SCHOOL DINIYAH PUTRI IN PEKANBARU - Idam Kholid Nasution; Triana Susanti; Muhammad Fikri (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2022)
تجريديهدف البحث لمعرفة فعالة تعليم اللغة العربية باستخدام الطريقة الإنتقائية في ترقية مهارة قراءة الطالبات فى المدرسة الثانوية الإسلامية الأهلية "دينية فتري" باكنبارو. ومنهج البحث هو بحث تجريبي الذي يتكون من تصميم خطة التعليم، والتطبيق، والملاحظة، وكذالك الإختبار. ومجتمع البحث يتكون من طالبات الفصل الثانى فى المدرسة الثانوية الإسلامية الأهلية "دينية فتري"باكنبارو. وعينته طالبات الصف الثانى "1" و "2" في تلك المدرسة. وموضوعه تعليم اللغة العربية باستخدام الطريقة الإنتقائية في ترقية مهارة القراءة. أدوات جمع البيانات هي الملاحظة والإختبار. نتائج البحث تدل على أنّ تعليم اللغة العربية باستخدام الطريقة الإنتقائية فعالا لترقية مهارة قراءة الطالبات فى المدرسة الثانوية الإسلامية الأهلية "دينية فتري"باكنبارو. AbtractIt is experimental research in which the researcher has directly participated as a teacher in the learning process. This research aims to prove the Study of Arabic by using Electic Method To Increase Student’s Ability to Read Arabic Language by finding the differences between students’ ability and those who have used Electic Method to Read the Arabic Language whit those who did not use it.  The problem setting of this research is, The subject of this research is an Arabic language teacher at Islamic Student Senior High School Diniyah Puteri in Pekanbaru, and the object is the Electic Method to Increase Student’s Ability to Read Arabic Language at Islamic Student Senior High School Diniyah Puteri in Pekanbaru. The population of this research is the second-grade students at Islamic Senior High School Diniyah Puteri in Pekanbaru. Those are in the second semester, and the sample is class IX 1 and XI 2. instruments used in collecting the data for this research are the following observations and tests. Based on the data analysis, it can be concluded that technic practice Theory effectively increases Student’s Ability to Read Arabic Language at Senior High School Diniyah Puteri in Pekanbaru.